2008
DOI: 10.1021/cb8000217
|View full text |Cite
|
Sign up to set email alerts
|

Ciliogenesis, Ciliary Function, and Selective Isolation

Abstract: In addition to their classic role in cell motility, certain cilia have sensory or signaling functions. In sea urchin embryos, short motile cilia randomly propel the early embryo, while a group of long, immotile cilia appear later, coincident with directional swimming and localized within a region that gives rise to the larval nervous system. Motile cilia can be selectively removed by treatment with a novel derivative of dillapiol, leaving the putative sensory cilia for comparative investigation and a gently de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…Previous studies have identified homologs for many DMT proteins (10,(35)(36)(37)(38); here, we show that this evolutionary conservation continues on a structural level. One exception is the strikingly different partition wall between Chlamydomonas and sea urchin flagella.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Previous studies have identified homologs for many DMT proteins (10,(35)(36)(37)(38); here, we show that this evolutionary conservation continues on a structural level. One exception is the strikingly different partition wall between Chlamydomonas and sea urchin flagella.…”
Section: Discussionsupporting
confidence: 73%
“…Assembly of the axoneme begins with the polymerization of tubulin and other proteins to form the A-tubules, extending directly from the plus-ends of the basal body A-tubules (32)(33)(34). Assembly of the A-tubule is complex and involves the following components: (i) αβ-tubulin with and without posttranslational modifications (6); (ii) the ribbon proteins tektins, Rib43a, Rib72/Efhc1, and Efhc2 (35)(36)(37)(38); (iii) the structural components MIP1a/MIP1b and MIP2a/ MIP2b, for which the protein composition has not yet been identified (10); and (iv) possibly other unidentified proteins. It is not known whether all these various proteins coassemble with tubulin to form the A-tubule or are added later.…”
Section: Discussionmentioning
confidence: 99%
“…These ∼50-kDa proteins have been characterized extensively from echinoderm and molluscan cilia (30, 32, 33, 35, 36, 51), and they have been identified in genomes ranging from protists to humans (27, 30). Tektins are expressed in mouse olfactory epithelial cells and photoreceptors that contain nonmotile, primary cilia (31), but they have not been found by proteomic studies of primary cilia of mouse kidney cells (52).…”
Section: Introductionmentioning
confidence: 99%
“…The swimming of marine larvae depends on ciliary propulsion and is critically important for feeding, escape responses (Strathmann, 2007;Stephens, 2008) and photosensitive vertical migration (Ooka et al, 2010). In sea urchin embryos, motile cilia are evident from the blastula stage, and rotatory movement by embryos can be observed in the fertilization envelope.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the swimming behavior of blastulae is organized to a considerable degree. For instance, sea urchin blastulae can swim by orienting their long apical tuft cilia in the target direction (Soliman, 1983a;Stephens, 2008). This suggests that swimming in sea urchin blastulae might be regulated by a distinctive mechanism that is not related to the 5HT-NS.…”
Section: Introductionmentioning
confidence: 99%